2011
DOI: 10.2528/pierc11052401
|View full text |Cite
|
Sign up to set email alerts
|

Quadri-Folded Substrate Integrated Waveguide Cavity and Its Miniaturized Bandpass Filter Applications

Abstract: In this paper, a quadri-folded substrate integrated waveguide (QFSIW) resonant cavity is proposed and investigated for the first time, which is able to reduce the circuit size by 89% compared with the conventional substrate integrated waveguide (SIW) resonant cavity. It has a two-layer configuration and a C-type coupling slot etched on the middle conductor layer. As an example, such a miniaturized resonant cavity is employed in the design of a four-order S-band SIW bandpass filter with the Chebyshev response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The authors of [46] used a quadri-folded SIW (QFSIW) for the first time to reduce the SIW dimensions by 89% of the conventional SIW structures. Figure.…”
Section: A Folded Siwmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of [46] used a quadri-folded SIW (QFSIW) for the first time to reduce the SIW dimensions by 89% of the conventional SIW structures. Figure.…”
Section: A Folded Siwmentioning
confidence: 99%
“…Coupling between the vertically connected resonators is optimized using a C-shaped slot in the middle copper layer. The concept of such coupling topology and miniaturization technique is verified by designing a fourth-order SIW bandpass filter [46].…”
Section: A Folded Siwmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, for studying the miniaturization of the SIW FA, we compare several methods of the miniaturization of the SIW filter. In the process of the SIW filter miniaturization, the SIW is firstly folded to form a multi-layer structure [39]- [41]. Then, a particular structure is etched on the top metal layer to form inductive and capacitive loading.…”
Section: Introductionmentioning
confidence: 99%
“…The latest trend in wireless communication system needs miniaturized filters in association with integrated multifunctional and multiband accomplishment for suppressing interference. It has been demonstrated that ring resonator based filters have attractive behaviour [2][3][4], but they have certain drawbacks such as large dimension and existence of higher order mode. Microstrip lines are compact and less expensive but resulting in non-immunity to the losses and parasitic crosstalk between lines.…”
Section: Introductionmentioning
confidence: 99%